2021
DOI: 10.3390/cancers13092011
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Analysis of the Short-Ranged Particle Emitter 161Tb for Radionuclide Therapy of Metastatic Prostate Cancer

Abstract: The aim of this study was to analyze the required absorbed doses to detectable metastases (Dreq) when using radionuclides with prostate specific membrane antigen (PSMA)-targeting radioligands to achieve a high probability for metastatic control. The Monte Carlo based analysis was performed for the clinically-used radionuclides yttrium-90, iodine-131, lutetium-177, and actinium-225, and the newly-proposed low-energy electron emitter terbium-161. It was demonstrated that metastatic formation rate highly influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…In the present study, S-values for terbium-161 were generated for different source distributions using skeletal dosimetry models. Numerous theoretical studies have reported significant local energy deposition of terbium-161, which is suitable when treating small tumors or disseminated disease [10][11][12][13]. Hindie et al performed dose calculations on spheres with diameters of 10-10,000 µm, whereas Bernhardt et al described the absorbed dose necessary for metastatic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, S-values for terbium-161 were generated for different source distributions using skeletal dosimetry models. Numerous theoretical studies have reported significant local energy deposition of terbium-161, which is suitable when treating small tumors or disseminated disease [10][11][12][13]. Hindie et al performed dose calculations on spheres with diameters of 10-10,000 µm, whereas Bernhardt et al described the absorbed dose necessary for metastatic control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the chemical similarities between these two radiolanthanides that facilitate the use of existing targeting agents, terbium-161 emits 12.4 conversion and Auger electrons below 50 keV per decay compared to only 1.2 in the case of lutetium-177 (Table 1) [9]. This is considered a desirable feature in targeted radionuclide therapies because the ionization density of the emitted electrons is increased at lower energies [10][11][12][13][14]. A number of theoretical and preclinical studies have suggested superior tumoricidal properties of terbium-161 compared to other radionuclides [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the biological redistribution of daughter radionuclides, different radionuclides have different emission particles and ranges that impact on the absorbed fraction of the radiation dose. Although short range alpha particles are absorbed completely locally, therapeutic radionuclides with beta particle emissions have a longer range and might only have a fraction absorbed locally [20]. In this work, we assumed the absorption fraction to be unity but, with more localized imaging data and a different radionuclide, this factor needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of tumor growth has been demonstrated using [ 149 Tb]Tb-PSMA-617 in TAT in mice bearing PC-3 PIP tumor cells [ 243 ]. In a preclinical study, [ 161 Tb]Tb-PSMA-617 was compared against [ 177 Lu]Lu-PSMA-617 in a PC-3 PIP xenograft model showing the superiority of 161 Tb vs. 177 Lu [ 244 , 245 ] opening the way for clinical translation. The additional therapeutic effect of 161 Tb due to Auger electrons was confirmed by a computational approach using a microdosimetry model [ 246 ].…”
Section: Potential Radionuclides For the Future Use Of Psma Inhibitorsmentioning
confidence: 99%